BK NEPHROPATHY AS A CAUSE FOR PROGRESSIVE LOSS OF FUNCTION IN A TRANSPLANTED KIDNEY - Severova, Galina; Stojanovska, Ana; Nikolov, igor; Rambabova- Bushletik, Irena; Petrushevska, Gordana; Spasovski, Goce (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
BK virus nephropathy is a serious complication of kidney transplantation. Although 10%â€“30% of kidney recipients have BK viremia, nephropathy occurs in approximately 2%.  We present a case of a 27-year-old woman with kidney transplant loss due to BK nephropathy. Transplantation was performed from a living donor mother, with a haploid HLA match. Treatment with basiliximab was induced and followed by a standard triple immunosuppressive therapy (corticosteroids, cyclosporin, mycophenolic acid). On the seventh day she was switched to tacrolimus (Tac), with serum Tac level up to 4,8 ng/ml. Ð¢hree months after transplantation, the first increase in creatinine (sCr) up to 263 mmol/L appeared. Ð¢he graft biopsy revealed: acute graft rejection, Banff classification (g2, and2, t2, a0, ah0, cg0, cc0, ct0, cd0) as well as an additional finding for BK polio infection (nuclear atypia in tubular epithelium, interstitial edema and mixed rich infiltration and acute tubulitis). The dose of Tac was reduced but also treatment with methylprednisolone pulse therapy was induced. Values for sCr were 173-280 mmol/L. After six months, a second biopsy was performed, with a finding of interstitial fibrosis and tubular atrophy. The Tac was switched to Cyclosporine. Five months later, the patient was hospitalized due to prolonged fever, sCr 500- 600 mmol/L. The third graft biopsy established chronic allograft nephropathy. The patient was treated with chronic hemodialysis. All microbiological tests were negative. Despite the antibiotic therapy, the patient remained febrileuntil graftectomy.  This case may be a rare example of systemic BK virus infection. Monitoring of BK infection, as well as modulating the therapy is of great importance for graft survival. Kew words :kidney transplantation, BK infection, immunosuppressive therapy, BK nephropathy  https://doi.org/10.55302/JMS2142015sa